The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.17691/stm2016.8.1.05
|View full text |Cite
|
Sign up to set email alerts
|

Biodistribution of Amine-Amide Chlorin e6 Derivative Conjugate with a Boron Nanoparticle for Boron Neutron-Capture Therapy

Abstract: The aim of the investigation was to study the biodistribution of amino-amide chlorin e 6 derivative conjugate with cobalt bis-dicarbollide as a potential boron transporter for the tasks of boron neutron-capture therapy.Materials and Methods. The experiments were carried out on Balb/c mice with induced murine colon carcinoma CT-26. Amino-amide chlorin e 6 derivative conjugate with cobalt bis-dicarbollide was administered intravenously, the dose being 5 and 10 mg/kg body mass. The sampling for microscopic study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…As for synthesized or commercialized 0D boron nanomaterials, suitable modications via surface ligand coupling with other molecules are oen adopted to improve various properties, structures, functions and application performances of products. 77,[129][130][131][132] Guo et al prepared BQDs via rst grinding with a mortar, followed by solvothermal treatment of ground boron powder, NaOH and N-methyl-2-pyrrolidone. 77 The dispersion of BQDs was mixed with PEG-NH 2 .…”
Section: Surface Ligand Coupling With Moleculesmentioning
confidence: 99%
See 3 more Smart Citations
“…As for synthesized or commercialized 0D boron nanomaterials, suitable modications via surface ligand coupling with other molecules are oen adopted to improve various properties, structures, functions and application performances of products. 77,[129][130][131][132] Guo et al prepared BQDs via rst grinding with a mortar, followed by solvothermal treatment of ground boron powder, NaOH and N-methyl-2-pyrrolidone. 77 The dispersion of BQDs was mixed with PEG-NH 2 .…”
Section: Surface Ligand Coupling With Moleculesmentioning
confidence: 99%
“…Volovetsky et al reported the chemical conjugation action of amine-amide chlorin e6 derivative with a boron nanoparticle. 130 The photosensitizer (chlorin e6) conjugated with boron particles via the amine-amide coupling of chlorin e6 with cobalt bis-dicarbollide (Fig. 10a and b).…”
Section: Surface Ligand Coupling With Moleculesmentioning
confidence: 99%
See 2 more Smart Citations